A silicon-containing lubricating composition with strong corrosion resistance and its preparation method and application

By developing a silicon-containing lubricating composition, using its direct adsorption properties to replace the phosphorus saponification tank, the problem of insufficient lubricity and corrosion resistance in the stainless steel wire stretching process is solved, and more efficient processing and longer corrosion resistance are achieved.

CN116333806BActive Publication Date: 2025-02-28YINGXING NEW MATERIALS (GUANGDONG) CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310278659.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-21
Publication Date
2025-02-28
Estimated Expiration
2043-03-21

AI Technical Summary

Technical Problem

In the existing stainless steel wire stretching process, a single drawing oil cannot completely remove oil stains or impurities on the surface of the wire, and some lubricants will turn black, deteriorate and smell during use. The treatment liquid with phosphorus saponification is short in corrosion resistance and low in drawing deformation.

Method used

A silicon-containing lubricating composition with strong corrosion resistance is developed, including film-forming agents, nanoparticles, extreme pressure agents, inorganic salts, anti-rust agents, surfactants, solvents and carboxymethyl cellulose, and the phosphorus saponification tank is replaced by direct adsorption to achieve integrated lubrication and corrosion protection.

Benefits of technology

The silicon-containing lubricating composition can significantly improve the lubricity and corrosion resistance of the wire surface, reduce the process, improve processing efficiency, and maintain good film integrity during the drawing process, extend the corrosion resistance time of the wire.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to the technical field of lubricants, and in particular to a silicon-containing lubricating composition with strong corrosion resistance, a preparation method thereof and an application thereof; the present application discloses a silicon-containing lubricating composition with strong corrosion resistance, comprising the following raw materials in weight percentage: 10-25% of a film former, 0.1-1.5% of nanoparticles, 1-5% of an extreme pressure agent, 3-7% of an inorganic salt, 1-5% of a rust inhibitor, 5-10% of a surfactant, 1-5% of a solvent, and the balance is water. The silicon-containing lubricating composition obtained in the present application contains a silicon polymer but does not contain phosphorus, can meet the requirements of phosphorus saponification integration and has good corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lubricants, and in particular to a silicon-containing lubricating composition with strong corrosion resistance, a preparation method and application thereof. Background Art

[0002] Phosphating is a commonly used method for corrosion resistance. Phosphating can form a film layer on the surface of the wire. After phosphating, it undergoes a layer of saponification. The generated phosphating saponification film layer can reduce the loss of subsequent processing molds and avoid scratches on the wire. It is currently the most widely used method. However, because phosphating saponification is a two-step process, and phosphating is acidic and saponification is alkaline, at least one water washing tank is required after phosphating, the process is long, and the phosphating saponification time is long.

[0003] Wire drawing is a metal processing technology that forces metal to pass through a die under pressure, compresses the metal cross-sectional area, and obtains the required cross-sectional shape and size. The factors that affect wire drawing mainly include the tensile strength of the wire, the degree of deformation, the friction coefficient between the wire and the grinding hole, the size of the wire die hole, the position of the wire die, etc. At present, in the stainless steel wire drawing process, wire drawing oil is usually used for processing. Since more oil stains or impurities will be generated on the surface of the wire during the drawing process of stainless steel wire, the use of a single wire drawing oil cannot guarantee that the oil stains or impurities on the surface of the wire after drawing are completely removed; and there are many types of wire drawing lubricants, and the performance varies greatly. Some wire drawing lubricants will turn black, deteriorate, and stink during use.

[0004] Patent CN2016100696746 discloses a phosphorus-free and chromium-free corrosion-resistant metal surface treatment agent, whose raw materials include nano zirconium dioxide dispersion, propionamide, bifluoride ammonium, polyvinyl alcohol, propylene glycol, siloxane, acetic acid, tea saponin, sodium citrate, sodium alginate, sodium hydroxide, silane coupling agent KH-550, film-forming agent, linseed oil and additives. By using nano zirconium dioxide dispersion as the main ingredient of the metal surface treatment agent of the present invention, and then adding propionamide, bifluoride ammonium, polyvinyl alcohol, propylene glycol, siloxane, acetic acid, tea saponin, sodium citrate, sodium alginate, sodium hydroxide, silane coupling agent KH-550, film-forming agent, linseed oil and additives as auxiliary additives of the metal surface treatment agent described in the application, the corrosion resistance and wear resistance of the metal surface treatment agent described in the application are further improved. The metal surface treatment agent described in the application does not contain phosphorus and chromium elements, does not pollute the environment, has good metal surface treatment effect, high efficiency and low cost. Although the metal surface treatment agent does not contain phosphorus and chromium elements, no specific corrosion resistance test results are given in the specific implementation method. The results have not been verified. In addition, through the corrosion resistance test of the wire after immersion but before drawing using the common phosphorus saponification treatment liquid on the market, the copper sulfate titration time is relatively short, usually less than 50s, and the actual corrosion resistance after drawing is less than 45 days. Therefore, the current phosphorus saponification treatment liquid has a short corrosion resistance time and low drawing deformation, which has great limitations. Therefore, for this situation, a phosphating soap integrated liquid with strong corrosion resistance is specially developed.

[0005] In view of this problem, the present invention develops a lubricating composition and a preparation method thereof that can realize the demand for integrated phosphorus saponification and has strong corrosion resistance and good lubricity. Summary of the invention

[0006] In order to overcome the shortcomings and deficiencies in the prior art, the purpose of the present application is to provide a silicon-containing lubricating composition with strong corrosion resistance and a preparation method and application thereof, wherein the silicon-containing lubricating composition can meet the requirements of integrated phosphorus saponification and has good corrosion resistance.

[0007] The purpose of this application is achieved through the following technical solutions:

[0008] The first purpose of the present application is to provide a silicon-containing lubricating composition with strong corrosion resistance, comprising the following raw materials in weight percentage:

[0009] The invention comprises 10-25% film-forming agent, 0.1-1.5% nanoparticles, 1-5% extreme pressure agent, 3-7% inorganic salt, 1-5% rust inhibitor, 5-10% surfactant, 1-5% solvent and the balance is water.

[0010] As a preferred solution, the film-forming agent is one or both of polysiloxane polymer and polyurethane acrylic resin.

[0011] Specifically, the commonly used polysiloxane polymer in this application is polydimethylsiloxane. Polydimethylsiloxane has a low surface energy and spreading coefficient. Polydimethylsiloxane can be cross-linked at low temperature to form a film under the action of a metal salt (inorganic salt) catalyst, forming a waterproof film on the surface of various materials (such as metal wires); the viscosity of the polydimethylsiloxane in this application is 500-700CP. If the viscosity of polydimethylsiloxane is too high, it is not easy to emulsify. If the viscosity of polydimethylsiloxane is too low, the lubricity is not good. As a film-forming agent, the amide bond of polyurethane acrylic resin can have good wire adsorption. Its CAS number is 68987-79-1, and the specific molecular weight is selected to be 500-600.

[0012] As a preferred solution, the nanoparticles are any one or more of aluminum oxide, boron nitride, and zirconium phosphide; and the particle size of the nanoparticles is 30-60 nm.

[0013] Specifically, in the present application, nanoparticles can be mixed in the solution to play a good supporting role and can reduce the friction of the wire surface when being pulled; if the particle size of the nanoparticles is lower than 30nm, the ability of the silicon-containing lubricating composition to adsorb the wire is weak, and if the particle size of the nanoparticles is higher than 60nm, the nanoparticles are not easily mixed in the silicon-containing lubricating composition, causing the silicon-containing lubricating composition to easily precipitate during the static process.

[0014] As a preferred solution, the extreme pressure agent is one or more of phosphate ester, chlorinated paraffin, and molybdenum dialkyl dithiocarbamate.

[0015] Specifically, in the present application, the extreme pressure agent is mainly used at the contact surface between the die and the wire during the drawing process. It can form a chemical reaction film with a higher melting point with the surface of the wire under high temperature and pressure conditions after high-speed drawing to improve lubricity.

[0016] As a preferred solution, the inorganic salt is one or two of sodium sulfate and sodium phosphate. In the present application, the inorganic salt is mainly used to balance the anions and cations in the bath solution. When the coating occurs, anions are first adsorbed on the surface of the wire, so the anion long chain and the surfactant will be preferentially adsorbed on the surface of the wire, and then an excess of cations will be generated at the moment of the reaction. The addition of the inorganic salt of the present application can well balance the ion balance at the interface.

[0017] As a preferred solution, the rust inhibitor is one or both of an amine rust inhibitor and an alcohol amine rust inhibitor.

[0018] Specifically, the amine rust inhibitor is any one of monoethylamine, diethylamine, and triethylamine, and the alcoholamine rust inhibitor is any one of monoethanolamine, diethanolamine, and triethanolamine.

[0019] As a preferred solution, the surfactant is one or both of anionic surfactant and nonionic surfactant.

[0020] Specifically, in the present application, the surfactant is mainly used to emulsify polysiloxane polymer or polyurethane acrylic resin. Anionic surfactants stabilize the emulsion by dispersing the double electric layer structure, and nonionic surfactants stabilize and disperse the emulsion by the hydration layer formed by the shielding effect, which can effectively increase the stability of the emulsion. The anionic surfactant is any one or any combination of alkyl diphenyl ether sulfonate disodium salt, sodium dodecyl polyoxyethylene ether sulfate, sodium dodecyl sulfate, and sodium dodecylbenzene sulfonate; the nonionic surfactant is any one or any combination of OP-10, NP-10, Tx-10, primary alcohol polyoxyethylene ether, and linear ethoxylated fatty alcohol.

[0021] As a preferred solution, the solvent is one or both of an ether solvent and an alcohol solvent; the silicon-containing lubricating composition further comprises 1-3% by weight of carboxymethyl cellulose.

[0022] In the present application, the addition of carboxymethyl cellulose can effectively increase the viscosity of the silicon-containing lubricating composition. At the same time, because carboxymethyl cellulose is a carboxylate in structure, it can have a synergistic effect with silicate and can be preferentially adsorbed on the wire to play a lubricating role.

[0023] Specifically, in the present application, the ether solvent is dipropylene glycol dimethyl ether, and the alcohol solvent is one or both of isopropanol and n-butanol.

[0024] The second object of the present application is to provide a method for preparing a silicon-containing lubricating composition with strong corrosion resistance, comprising the following steps:

[0025] S1. Prepare the materials according to the weight of each raw material of the silicon-containing lubricating composition;

[0026] S2. The surfactant and the film-forming agent are mixed at a temperature of 80-90 ° C, heated with stirring for 20-30min, an appropriate amount of water is added, the stirring speed is 800-1200rpm, and the emulsification is performed for 0.6-1h. After emulsification, a mixed solution A is obtained and set aside;

[0027] S3. The extreme pressure agent, rust inhibitor, inorganic salt, solvent, appropriate amount of water are mixed and stirred to obtain a mixed solution B for standby use;

[0028] S4. Mix the mixed solution A and the mixed solution B and stir evenly; add the nanoparticles and ultrasonically vibrate for 30-40 min at 40-50 ° C; after the ultrasonic treatment, a mixed solution C is obtained and set aside;

[0029] S5. Add carboxymethyl cellulose to the obtained mixed solution C, mix evenly, and then add the remaining water and mix thoroughly to obtain a silicon-containing lubricating composition.

[0030] The third purpose of the present application is to provide an application of a silicon-containing lubricating composition, wherein the silicon-containing lubricating composition is used in the drawing process of a metal wire, and the silicon-containing lubricating composition is derived from the silicon-containing lubricating composition described above or is a silicon-containing lubricating composition prepared according to the above preparation method.

[0031] The beneficial effects of this application are:

[0032] 1. The silicon-containing lubricating composition obtained in the present application does not use the phosphating and saponifying method to generate the phosphating saponification film layer in the raw materials, nor does it use the phosphating and saponifying lubrication method. Instead, it uses the silicon-containing lubricating composition to directly adsorb, replacing the phosphating saponification tank for processing in one step, thereby reducing the process and improving the processing efficiency.

[0033] 2. The silicon-containing lubricating composition obtained in the present application has significantly improved film-forming property, adsorption property and corrosion resistance compared with conventional lubricants by adding polysiloxane polymer and polyurethane acrylic resin. DETAILED DESCRIPTION

[0034] In order to facilitate the understanding of those skilled in the art, the present invention is further described below in conjunction with embodiments, and the contents mentioned in the implementation modes are not intended to limit the present invention.

[0035] As used herein, "and / or" includes the term of any and all combinations of one or more associated listed items. The terms used herein are only used to describe specific embodiments and are not intended to limit the present invention. As used herein, the singular forms "a", "an", "an" and "the" are also intended to include the plural forms, unless the context clearly indicates otherwise. It is further understood that "including", when used in this specification, specifies the stated features, integers, steps, operations, elements and / or compositions, but does not exclude the existence or addition of one or more other features, integers, steps, operations, elements, compositions and / or combinations thereof.

[0036] Unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the invention belongs. It is further understood that terms, such as defined in commonly used dictionaries, are interpreted in accordance with their meanings in the context of the relevant art and are not in an idealized or overly formal sense unless explicitly so defined herein.

[0037] The exemplary invention described herein may appropriately lack any one or more element limitations that are not specifically disclosed herein. Therefore, the terms "comprise", "include", "contain", etc. should be understood broadly and non-restrictively. In addition, the terminology used herein is used as a description, not a limitation, and it is unintentional to use these terminology expressions that do not include any equivalent characteristics, but only describe some of their characteristics, but various modifications are possible within the scope of the present invention according to the rights. Therefore, although the present invention has been specifically disclosed by preferred embodiments and optional features, the modifications disclosed herein to embody the changes of the present invention may be recorded by those skilled in the art, and such modifications and changes will be considered to be within the scope of the present invention.

[0038] The raw materials or reagents used in the embodiments of the present invention and the comparative examples are all purchased from mainstream manufacturers in the market. Those without indicating the manufacturer or the concentration are all analytically pure raw materials or reagents that can be routinely obtained, and there are no special restrictions as long as they can play the expected role. The three-necked flask and condensing device and other instruments and equipment used in this embodiment are all purchased from major manufacturers in the market, and there are no special restrictions as long as they can play the expected role. If specific techniques or conditions are not indicated in this embodiment, the techniques or conditions described in the literature in this area or the product instructions are carried out.

[0039] Example 1

[0040] A method for preparing a silicon-containing lubricating composition with strong corrosion resistance comprises the following steps:

[0041] S1. Prepare the materials according to the weight of each raw material of the silicon-containing lubricating composition;

[0042] S2. Take a three-necked flask, place a thermometer in one mouth, place a condenser in one mouth, and use a mechanical stirring mouth. Add 10 g of silicone polymer (polydimethylsiloxane, viscosity controlled at 500-700 CP), 20 g of polyurethane acrylic resin (molecular weight controlled at 500-600), 2 g of NP-10, and 3 g of linear ethoxylated fatty alcohol to the three-necked flask, mix them together as a pre-emulsion, heat and maintain at 90 ° C, heat and stir for 20 min, then add water three times for a total of 20 g, and keep the mechanical stirring speed at 800 rpm, emulsify for 1 h, and wait for it to be converted from a hydrophobic substance into a milky white emulsion-like substance; after the emulsification is completed, a mixed solution A is obtained for standby use;

[0043] S3. Take another beaker, add 3g of sodium sulfate, add 30g of water to dissolve, then add 1g of phosphate, 1g of monoethylamine, 2g of triethanolamine, 2g of propanol, and 3g of dipropylene glycol dimethyl ether, mix and stir well to obtain a mixed solution B for standby use.

[0044] S4. The mixed solution A and the mixed solution B were mixed and stirred evenly, 1 g of aluminum oxide (particle size 30 nm) was added, and ultrasonic vibration was performed at 40 ° C for 40 min to completely mix; after the ultrasonic treatment, a mixed solution C was obtained and set aside;

[0045] S5. Add 2 g of carboxymethyl cellulose to the obtained mixed solution C, add water to a total weight of 100 g, and mix well to obtain a silicon-containing lubricating composition.

[0046] The silicon-containing lubricating composition obtained in this example is in the form of an emulsion, has a dynamic viscosity of 420 N·s / ㎡, and has no stratification phenomenon after standing.

[0047] Usage: The silicon-containing lubricating composition is diluted to a lubricating liquid with a weight concentration of 15%. When heated to 70°C, the test data is that the sugar content is 5.4 and the dynamic viscosity is 64N·s / ㎡.

[0048] Use process: wire pickling → water washing → soaking and coating (lubricating liquid with a weight concentration of 15% in this embodiment) → drying → drawing;

[0049] Specifically, the wire used is 22A, with a wire diameter of 6mm. After pickling and washing, it is soaked (15% weight concentration of lubricant in this embodiment) for 6 minutes, taken out, and dried. The appearance is observed to have a layer of shiny transparent film, which is uniform and evenly coated on the wire. The film weight is 12.2g / m 2 .

[0050] Drawing results: When the wire is drawn to 2mm through multiple dies, the surface of the wire is still bright and the base material is not exposed.

[0051] Corrosion resistance test of wire after immersion but before drawing: copper sulfate titration time is 100s, and the actual corrosion resistance after drawing is 90 days.

[0052] Example 2

[0053] S1. Prepare the materials according to the weight of each raw material of the silicon-containing lubricating composition;

[0054] S2. Take a three-necked flask, place a thermometer in one mouth, place a condensing device in one mouth, and use a mechanical stirring mouth. Add silicone polymer (polydimethylsiloxane, viscosity controlled at 550-650CP) 25g, polyurethane acrylic resin (molecular weight controlled at 550-600) 18g, alkyl diphenyl ether sulfonate disodium salt 3g, primary alcohol polyoxyethylene ether 1g, dodecyl polyoxyethylene ether sodium sulfate 5g and mix together as a pre-emulsion, heat and maintain at 90 ° C, heat and stir for 30min, then add water three times for a total of 30g, while the mechanical stirring speed is maintained at 1200rpm, emulsify for 1h, until it is converted from a hydrophobic substance into a milky white emulsion-like substance; after the emulsification is completed, a mixed solution A is obtained for standby use;

[0055] S3. Take another beaker, add 7g of sodium phosphate, add 26g of water to dissolve, then add 5g of phosphate ester, 4g of triethanolamine, 1g of isopropanol, and 4g of dipropylene glycol dimethyl ether respectively, mix and stir well; obtain mixed solution B for standby use.

[0056] S4. The mixed solution A and the mixed solution B were mixed and stirred evenly, 1.5 g of aluminum oxide (particle size 60 nm) was added, and ultrasonic vibration was performed at 40 ° C for 40 min until the solution was completely mixed; after the ultrasonic treatment, a mixed solution C was obtained and set aside;

[0057] S5. Add 3 g of carboxymethyl cellulose to the obtained mixed solution C, add water to a total weight of 100 g, and mix well to obtain a silicon-containing lubricating composition.

[0058] The silicon-containing lubricating composition obtained in this example is in the form of an emulsion, with a dynamic viscosity of 610 N·s / ㎡, and no stratification phenomenon after standing.

[0059] Usage: The silicon-containing lubricating composition is diluted to a lubricating liquid with a concentration of 10% by weight. When heated to 70°C, the test data shows that the sugar content is 5.1 and the dynamic viscosity is 56N·s / ㎡.

[0060] Use process: wire pickling → water washing → soaking and coating (lubricating liquid with a 10% weight concentration in this embodiment) → drying → drawing;

[0061] The wire used is 18A, with a wire diameter of 6mm. After pickling and washing, it is soaked in (10% weight concentration of lubricant in this embodiment) for 6 minutes, taken out, and dried. The appearance is observed to have a layer of shiny transparent film, which is uniform and evenly coated on the wire. The film weight is 11.5g / m 2 .

[0062] Drawing results: When the wire is drawn to 2mm through multiple dies, the surface of the wire is still bright and the base material is not exposed.

[0063] Corrosion resistance test of the wire after immersion but before drawing: the copper sulfate titration time is 110s, and the actual corrosion resistance after drawing is 105 days.

[0064] Example 3

[0065] S1. Prepare the materials according to the weight of each raw material of the silicon-containing lubricating composition;

[0066] S2. Take a three-necked flask, place a thermometer in one mouth, place a condensing device in one mouth, and use a mechanical stirring mouth. Add silicone polymer (polydimethylsiloxane, viscosity controlled at 600-700CP) 10g, polyurethane acrylic resin (molecular weight controlled at 500-550) 10g, OP-102g, linear ethoxylated fatty alcohol 1g, sodium dodecyl polyoxyethylene ether sulfate 1g, sodium dodecylbenzene sulfonate 1g to the three-necked flask and mix them together as a pre-emulsion, and heat and maintain at 80 ° C., heat and stir for 30min, then add water three times for a total of 20g, while the mechanical stirring speed is maintained at 800rpm, emulsify for 40min, and wait for it to be converted from a hydrophobic substance into a milky white emulsion-like substance; after the emulsification is completed, a mixed solution A is obtained for standby use;

[0067] S3. Take another beaker, add 3g of inorganic sodium phosphate, add 22g of water to dissolve, then add 1g of phosphate ester, 0.8g of triethanolamine, 0.4g of n-butanol, and 0.6g of dipropylene glycol dimethyl ether respectively, mix and stir well; obtain mixed solution B for standby use.

[0068] S4. The mixed solution A and the mixed solution B were mixed and stirred evenly, 0.1 g of boron nitride (particle size 30 nm) was added, and ultrasonic vibration was performed at 40 ° C for 40 min until the solution was completely mixed; after the ultrasonic treatment, a mixed solution C was obtained and set aside;

[0069] S5. Add 1 g of carboxymethyl cellulose to the obtained mixed solution C, add water to make the total weight 100 g, mix well, and obtain a silicon-containing lubricating composition.

[0070] The silicon-containing lubricating composition obtained in this example is in the form of an emulsion, has a dynamic viscosity of 483 N·s / ㎡, and has no stratification phenomenon after standing.

[0071] Usage: dilute the silicon-containing lubricating composition to a lubricating liquid with a concentration of 8% by weight, heat to 70°C, and the test data shows that the sugar content is 4.9 and the dynamic viscosity is 34N·s / ㎡.

[0072] Use process: wire pickling → water washing → soaking and coating (8% weight concentration of lubricating liquid in this embodiment) → drying → drawing;

[0073] The wire used is 45Cr with a wire diameter of 6mm. After pickling and washing, it is soaked in (8% weight concentration lubricant in this embodiment) for 4 minutes, taken out, dried, and observed to have a layer of shiny transparent film. The film layer is uniform and evenly coated on the wire, and the film weight is 12g / m 2 .

[0074] Drawing results: When the wire is drawn to 2mm through multiple dies, the surface of the wire is still bright and the base material is not exposed.

[0075] Corrosion resistance test of the wire after immersion but before drawing: the copper sulfate titration time is 100s, and the actual corrosion resistance after drawing is 101 days.

[0076] Comparative Example 1:

[0077] Phosphorus saponification integrated lubricant currently on the market.

[0078] The lubricant is in powder form and takes a long time to dissolve. The grooving concentration is 15% (15g lubricant + 85g water), the operating temperature is 90°C, the test data shows a sugar content of 5.5 and a dynamic viscosity of 32N·s / ㎡.

[0079] The wire used is 22A, with a wire diameter of 6mm. After pickling and washing, it is soaked for 5 minutes, taken out, and dried. The appearance is observed to have a film layer, but the color of the film layer is darker and there is no oil brightness. The film weight is 8g / m 2 .

[0080] When the wire is drawn to 2 mm through multiple dies, there is still basically no film layer on the surface of the wire, but there are local scratches.

[0081] Corrosion resistance test of wire after immersion but before drawing: copper sulfate titration time is 40s, and the actual corrosion resistance after drawing is 40 days.

[0082] Comparative Example 2

[0083] No polyurethane acrylic resin was added, and the remaining raw material composition was consistent with that in Example 1 (the amount of water was adaptively adjusted); the preparation process and process parameters were consistent with those in Example 1.

[0084] The silicon-containing lubricating composition prepared in this comparative example is in the form of an emulsion, has a dynamic viscosity of 380 N·s / ㎡, and has no stratification phenomenon after standing.

[0085] Usage: The silicon-containing lubricating composition is diluted to a lubricating liquid with a weight concentration of 14.5%. When heated to 70°C, the test data is a sugar content of 6 and a dynamic viscosity of 24N·s / ㎡.

[0086] Use process: wire pickling → water washing → soaking and coating (lubricating liquid with a weight concentration of 14.5% in this comparative example) → drying → drawing;

[0087] Specifically, the wire material used is 45Cr, the wire diameter is 10mm, after pickling and water washing, it is soaked (14.5% by weight concentration of lubricant in this comparative example) for 6 minutes, taken out, dried, and observed that there is a layer of glossy transparent film on the appearance, and the film weight is 8.5g / m 2 .

[0088] Drawing results: When the wire is drawn to 2mm through multiple dies, there is a small amount of film layer on the surface of the wire and obvious scratches in some parts.

[0089] Corrosion resistance test of wire after immersion but before drawing: copper sulfate titration time is 50s, and the actual corrosion resistance after drawing is 48 days.

[0090] Comparative Example 3

[0091] In step S5, no carboxymethyl cellulose was added, and the remaining conditions were the same as those in Example 1.

[0092] The silicon-containing lubricating composition prepared in this comparative example is in the form of an emulsion, has a dynamic viscosity of 280 N·s / ㎡, and has no stratification phenomenon after standing.

[0093] Usage: The silicon-containing lubricating composition is diluted to a lubricating liquid with a weight concentration of 16.5%. When heated to 70°C, the test data is that the sugar content is 5.8 and the dynamic viscosity is 10N·s / ㎡.

[0094] Use process: wire pickling → water washing → soaking and coating (lubricating liquid with a weight concentration of 16.5% in this comparative example) → drying → drawing;

[0095] Specifically, the wire material used is 22A, the wire diameter is 6mm, after pickling and washing, it is soaked (16.5% weight concentration of lubricating liquid in this comparative example) for 6 minutes, taken out, dried, and observed that there is a layer of glossy transparent film layer, the film weight is 10g / m 2 .

[0096] Drawing results: When the wire is drawn to 2mm through multiple dies, there is a small amount of film layer on the surface of the wire and slight scratches in some parts.

[0097] Corrosion resistance test of the wire after immersion but before drawing: the copper sulfate titration time is 63s, and the actual corrosion resistance after drawing is 65 days.

[0098] The above embodiments are preferred implementation schemes of the present application. In addition, the present application may also be implemented in other ways. Any obvious replacement without departing from the concept of the present application is within the protection scope of the present application.

Claims

1. An application of a silicon-containing lubricating composition, characterized in that: The silicon-containing lubricating composition is used in the drawing process of metal wires, and the silicon-containing lubricating composition comprises the following raw materials in percentage by weight: Film former 10-25%, nanoparticles 0.1-1.5%, extreme pressure agent 1-5%, inorganic salt 3-7%, rust inhibitor 1-5%, surfactant 5-10%, solvent 1-5%, the balance is water; The film-forming agent is composed of polysiloxane polymer and polyurethane acrylic resin; the polyurethane acrylic resin has a CAS number of 68987-79-1 and a molecular weight of 500-600; The silicon-containing lubricating composition further comprises 1-3% by weight of carboxymethyl cellulose; The rust inhibitor is one or both of an amine rust inhibitor and an alcohol amine rust inhibitor; the amine rust inhibitor is any one of monoethylamine, diethylamine, and triethylamine; the alcohol amine rust inhibitor is any one of monoethanolamine, diethanolamine, and triethanolamine; The nanoparticles are any one or more of aluminum oxide, boron nitride, and zirconium phosphide; and the particle size of the nanoparticles is 30-60 nm.

2. The use according to claim 1, characterized in that: The extreme pressure agent is a phosphate ester.

3. The use according to claim 1, characterized in that: The inorganic salt is one or both of sodium sulfate and sodium phosphate.

4. The use according to claim 1, characterized in that: The surfactant is one or both of anionic surfactant and nonionic surfactant.

5. The use according to claim 1, characterized in that: The solvent is one or both of an ether solvent and an alcohol solvent.

6. The use according to claim 1, characterized in that: The method for preparing the silicon-containing lubricating composition comprises the following steps: S1. Prepare the materials according to the weight of each raw material of the silicon-containing lubricating composition; S2. The surfactant and the film-forming agent are mixed at a temperature of 80-90 ° C, heated with stirring for 20-30min, an appropriate amount of water is added, the stirring speed is 800-1200rpm, and the emulsification is performed for 0.6-1h. After emulsification, a mixed solution A is obtained and set aside; S3. The extreme pressure agent, rust inhibitor, inorganic salt, solvent, appropriate amount of water are mixed and stirred to obtain a mixed solution B for standby use; S4. Mix the mixed solution A and the mixed solution B and stir evenly; add the nanoparticles and ultrasonically vibrate at 40-50°C for 30-40min; after the ultrasonic treatment, a mixed solution C is obtained and set aside; S5. Add carboxymethyl cellulose to the obtained mixed solution C, mix evenly, and then add the remaining water and mix thoroughly to obtain a silicon-containing lubricating composition.

Citation Information

Patent Citations

  • Aqueous coating agent composition and aqueous coating composition comprising same for lubricating film

    CN111032803A

  • Titanium alloy wire high-temperature drawing oil-based lubricant and preparation method thereof

    CN111778093A

  • Film-forming agent and coated film

    JP2002363593A